Preliminary Study on Extraction of Bio-flocculants from Okra and Chinese Yam - Lee, Chai Siah; Chong, Mei Fong; Robinson, John; Binner, Eleanor (ASEAN Journal of Chemical Engineering, 2015)
Natural bio-flocculants were extracted from okra and Chinese yam using water extraction method, and the extract yield and their flocculating abilities were evaluated. Results showed that extraction of okra with seed removal and incubation followed by freeze drying enhanced the extract yield by 91% and improved the flocculating ability greatly by achieving solids removal of above 99% when compared with extraction without incubation and followed by oven drying. The effect of an incubation step was further investigated by using Chinese yam. With incubation, a higher extract yield of 2.95% was obtained compared with the extraction without incubation at 2.13% and high flocculating ability was achieved at 99.5% solids removal. To further investigate the application of bio-flocculants, the samples with the highest extract yield and flocculating ability were selected for a case study focusing on treatment of oleochemical wastewater. Yam bio-flocculant showed its flocculating activity with 80% solids removal when it was coupled with coagulant without pH alteration. However, pH adjustment was required for okra bio-flocculant. In conclusion, highly efficient okra and yam bio-flocculants were successfully extracted and their applicability to wastewater treatment was proven.